Suffering, Virtue, and Character: Why the Science of Virtue Matters - Wright, Jennifer Cole; Snow, Nancy E.; Warren, Michael T. (Acta Philosophica, 2020)
One of the main arguments that has been given for the importance of virtue is that it is not only important for, but is in fact constitutive of, a life well-lived, necessary for human wellbeing and flourishing. Yet, human life is also profoundly fragile, often filled with, and always vulnerable to, suffering. Thus, we must ask: what role does virtue play in our suffering, in how we face it, manage it, and survive it? Recent work in philosophy and psychology has argued for an important potential relationship between suffering and virtue, but the nature of this relationship is not well understood. In this paper, we lay out a philosophically and empirically rigorous approach to conceiving of and measuring virtue as a particular type of personality trait, and then discuss the implications of our account for aiding philosophers and psychologists in their quest to understand the relationship between suffering and virtue.